Alendronate treatment in children with osteogenesis imperfecta - (:unkn) unknown (INDIAN ACAD PEDIATRICS, 2008)
Background: Recent studies reported beneficial effect of cyclical intravenous administration of pamidronate in children and adolescents With osteogenesis imperfecta (OI). However, this treatment requires frequent hospital admissions and is relatively expensive. Alendronate is an oral bisphosphonate effectively used in adults with osteoporosis. Experience with alendronate treatment in children with OI is limited Aims: To report our experience with alendronate in children with OI. Methods: 12 children with 01 (7 with type 1, 4 with type III and I with type IV; 7 boys, 5 girls) aged 1.8 to 15.4 years (7.9 +/- 4.4 yrs),were included in this retrospective study. The patients were treated with alendronate in a dose of 5-10 mg/day along with calcium (500 mg/day) and vitamin D (400-1000 IU/day) supplements for 19.8 +/- 11.3 months (range: 7-46 months). Serum calcium (Ca), phosphorus (P), alkaline phosphatase (ALP), osteocalcin (OC), pyrilinks-D and urinary Ca/Cr ratio were studied 3 monthly and bone mineral density (BMD) by DXA on 612 monthly basis. Results: Fracture rate of the patients significantly decreased after treatment (1.2 +/- 1.5 vs. 0.16 +/- 0.32 peryear, P<0.05). Treatment improved bone density in each individual case. Z-scores of lumbar DXA (L2-L4) significantly increased during treatment (-4.60 +/- 1.30 vs -2.47 +/- 1.52, P< 0.05). Urinary pyrilinks-D decreased with treatment (90.8 +/- 136.3 vs. 35.1 +/- 29.9, P < 0. 05). Serum Ca, P, ALP, OC and urinary Ca/Cr did not change significantly during treatment. Conclusion: We conclude that alendronate is effective, safe and practical alternative to intravenous bisphosphonates in treatment of children with OI.
Keywords: alendronate; bisphosphanates; osteogenesis imperfecta; BISPHOSPHONATE THERAPY; BONE-DISEASE; I COLLAGEN; PAMIDRONATE; FEATURES